Narrative Review of Infection Control Knowledge and Attitude among Healthcare Workers - Abdurahman AlJohani; Karmegam Karuppiah; Alya Al Mutairi; Abbas Al Mutair (Springer, 2020)
Background: Infection is one of the major threats to Healthcare Workers (HCW) worldwide. It exposes HCW to more than 20 kinds of blood-borne pathogen infections, especially the most severe cases, namely Hepatitis B Virus (HBV), Hepatitis C Virus (HCV), and Human Immunodeficiency Virus (HIV). The impact of infection about HCWs' health, clinical burden, national economic burden, and humanistic burden suggests the importance of further investigation and discussion on this topic. Aims: This paper aimed to discuss literature on infection control knowledge and attitudes among HCWs and potential factors contributing to infection control. Method: For this narrative review Proquest, Medline, and Up To Date have been utilized to search articles about infection control knowledge and attitudes among healthcare workers and potential factors contributing to infection control. The search was narrowed to article between 2000 and 2018. A total of 400 materials were initially identified to be potentially relevant for the review. A total of 28 articles were included, and they were found to match the inclusion criteria. Results: Results from the reviewed studies showed that there was a high-level knowledge in terms of precautionary measures and compliance with needle safety precautions while staff attitude achieved above average. Weak positive correlation was found between staff attitude and precautionary measures, while moderate positive correlation was found between precautionary measures and compliance with needle safety precautions. Only precautionary measures were found to significantly influence compliance with needle safety precautions, in which higher precautionary measures, resulted in higher compliance with needle safety precautions.